2018
DOI: 10.1016/j.imr.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio as a predictor of myocardial damage and cardiac dysfunction in acute coronary syndrome patients

Abstract: BackgroundNeutrophil to lymphocyte ratio (NLR) in peripheral blood is established to correlate with the morbidity and mortality of heart disease patients. We aimed to define the severity of inflammation (NLR) by observing the association of NLR with cardiac functions or myocardial damage parameters in patients with acute myocardial infarction.MethodsData from 715 patients who underwent percutaneous coronary intervention (PCI) within 72 hours of incidence in 2016 were analysed retrospectively.ResultsThe NLR ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
54
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 40 publications
12
54
0
2
Order By: Relevance
“…Similar increment in NLR was observed in disease conditions . Previously, we have shown that mean NLR in 715 acute myocardial infarction patients on admission without failure or infection was 2.76; mean NLR was 2.65 when GRACE risk score was 100 and NLR was >6.5 when GRACE risk score was over 140 . Arbel et al explored that NLR (>6.5) was associated with lower EF and increased 30 days and 5‐year mortality .…”
Section: Discussionsupporting
confidence: 66%
“…Similar increment in NLR was observed in disease conditions . Previously, we have shown that mean NLR in 715 acute myocardial infarction patients on admission without failure or infection was 2.76; mean NLR was 2.65 when GRACE risk score was 100 and NLR was >6.5 when GRACE risk score was over 140 . Arbel et al explored that NLR (>6.5) was associated with lower EF and increased 30 days and 5‐year mortality .…”
Section: Discussionsupporting
confidence: 66%
“…The NLR as an indicator of systemic inflammation is associated with poor clinical outcomes in cardiovascular diseases such as acute coronary syndrome [ 15 ]. Recent evidence showed that high NLR was associated with an increased risk of mortality and complications in post-acute myocardial infarction [ 16 , 17 ]. Turcato et al [ 18 ] showed that the values of NLR and PLR were higher in acute decompensated heart failure patients who died within 30 days…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, neutrophil‐to‐lymphocyte ratio (NLR) has been proved of great value with a significant correlation with systemic inflammation reaction in several autoimmune diseases . Because NLR can be easily obtained at low cost through an automatic hematology analyzer, many research groups have further confirmed the value of NLR in predicting disease severity and worse clinical outcomes in a variety of diseases, including cerebrovascular diseases, cardiovascular diseases, and neoplasm . Besides, cumulative evidence has suggested that NLR was associated with AP and better than other serum markers in predicting severity and prognosis of AP.…”
Section: Introductionmentioning
confidence: 99%